Foreign Currency Deposits in Developing Countries-Origins and Economic Implications. (IMF Working Papers; Working Paper ;, 1987)
The growing importance of foreign currency deposits (FCDs) in some developing countries has raised numerous issues, particularly regarding the effectiveness of economic policies. This paper discusses factors that influence the emergence of FCDs and their impact on key macroeconomic relations. It is shown that while FCDs render more visible the changes in the economic structure occasioned by the shift in residents' portfolio asset preferences, these changes essentially reflect currency substitution that often prevails prior to the introduction of FCDs. Moreover, FCDs provide only limited scope for effectively addressing the external and domestic imbalances that contribute to the growth in currency substitution.